An Analysis Of Factors Affecting English Department Students In Thesis Writing THESIS WRITING - Sandiarsa S., K. Dedy; Hanan, Ahmad (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study aimed to analyze factors affecting students in writing thesis. This research was qualitative research with descriptive design. The participants of this research were 20 students of the eighth semester students of English Department Program at FBMB UNDIKMA 2022/2023. The researchers used questionnaire and interview as the instruments. The instruments were focused on the three factors: psychological, sociocultural and linguistics factors. Based on the result of questionnaire, it showed that in psychological factor the students obtained 75% score, meanwhile in sociocultural factor the students obtained 71% score, and the highest factor affecting students in writing thesis was linguistic factor which reaching the score of 80%. Based on the average of those three factors showed that the students obtained 76% score; it means that the students have high score criteria. Moreover, based on the interviews showed that there were no students answers disagree toward the questions of interview. Alternatively, it can be concluded that the result of questionnaire and interview was matched. Consequently, it can be suggested that, the eighth semester students of English Department Program at FBMB UNDIKMA have to pay more attention in linguistic factor, since this factor was the highest percentage that can interfere graduation process.